1988
DOI: 10.1073/pnas.85.11.3865
|View full text |Cite
|
Sign up to set email alerts
|

Glucose stimulates proinsulin biosynthesis by a dose-dependent recruitment of pancreatic beta cells.

Abstract: Glucose is a well-known stimulus of proinsulin biosynthesis. In purified beta cells, the sugar induces a 25-fold increase in the synthesis of insulin immunoreactive material over 60-min incubation. Autoradiographic analysis of the individual cells shows that this effect is achieved via dose-dependent recruitment of pancreatic beta cells to biosynthetic activity. Recruitment of beta cells is also seen in isolated islets exposed to glucose. The sigmoidal dose-response curve for glucose-induced proinsulin biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
251
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(261 citation statements)
references
References 37 publications
7
251
0
3
Order By: Relevance
“…Under stimulatory conditions, production of insulin may represent up to 50% of total protein production, placing an enormous burden on the ER [50]. As a consequence, beta cells are in a constant state of mild ER-stress, characterised by high basal expression of UPR transducers such as IRE1α, allowing them to adapt efficiently to the ever changing insulin demand [3].…”
Section: Discussionmentioning
confidence: 99%
“…Under stimulatory conditions, production of insulin may represent up to 50% of total protein production, placing an enormous burden on the ER [50]. As a consequence, beta cells are in a constant state of mild ER-stress, characterised by high basal expression of UPR transducers such as IRE1α, allowing them to adapt efficiently to the ever changing insulin demand [3].…”
Section: Discussionmentioning
confidence: 99%
“…Half-maximal synthesis occurred at 5.4 mM glucose and the V max was 42.971.4 Â 10 3 cpm/mg DNA (n¼6), not significantly different from that for human islets. 21,22 The ratio of (pro)insulin synthesis to total protein synthesis was 0.065 at 2.5 mM glucose, 0.196 at 10 mM glucose and 0.213 at 20 mM glucose. …”
Section: (Pro)insulin Synthesismentioning
confidence: 97%
“…6 In contrast to the dose-response curve for insulin secretion, that for insulin synthesis was exactly the same as that which occurs in pancreatic b cells. 21,22 This implies that different metabolites of glucose are responsible for the secretion of insulin and translation of the insulin message from the nucleus. …”
Section: Insulin-producing Liver Cells Be Tuch Et Almentioning
confidence: 99%
“…For instance, beta cells respond unequally to glucose stimulation in terms of insulin secretion and biosynthetic activity [12,14,15]. It has been suggested that intercellular contacts coordinate the functioning of beta cells by homogenising and synchronising their activities.…”
Section: Introductionmentioning
confidence: 99%